Electronic structural studies on the improved thermal stability of Li(Ni0.8Co0.15Al0.05)O-2 by ZrO2 coating for lithium ion batteries - Kim, Ji-Young; Kim, Sang Hoon; Kim, Dong Hyun; Susanto, Dieky; Kim, Se Young; Chang, Won-Young; Cho, Byung Won; Yoon, Won-Sub; Bak, Seong Min; Yang, Xiao Qing; Nam, Kyung Wan; Chung, Kyung Yoon (SPRINGER, 2017)
The electronic structures of bare and ZrO2-coated Li(Ni0.8Co0.15Al0.05)O-2 electrode systems were investigated using a combination of time-resolved X-ray diffraction and soft X-ray absorption spectroscopy (XAS) techniques. The ZrO2 coating on the surface of Li(Ni0.8Co0.15Al0.05)O-2 was effective in elevating the onset temperature of the dissociation of charged Li-0.33(Ni0.8Co0.15Al0.05)O-2, which will enhance the safety of Li-ion cells. Soft XAS spectra of the Ni L-II,L-III-edge in the partial electron yield mode were obtained, which showed that the enhanced electrochemical properties and thermal stability of the cathode materials by ZrO2 coating can be attributed to the suppression of unwanted Ni oxidation state changes at the surface. The electronic structural effects of a ZrO2 coating on Li(Ni0.8Co0.15Al0.05)O-2 were examined by soft X-ray absorption spectroscopy. The coating stabilized the Ni oxidation state at the electrode surface against decomposition. [GRAPHICS] .
Keywords: X-RAY-ABSORPTION; NICKEL-OXIDE DERIVATIVES; TIME-RESOLVED XRD; IN-SITU XRD; LI-ION; CATHODE MATERIALS; CYCLING PERFORMANCE; CAPACITY RETENTION; SPECTROSCOPY; LICOO2